PENGARUH MEDIA TUMBUH BEBERAPA LIMBAH SERBUK KAYU GERGAJIAN TERHADAP PERTUMBUHAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Fauzia, Fauzia; Yusran, Yusran; Irmasari, Irmasari (Warta Rimba, 2014)
The objectives of this study were to investigate the effects of some sawdust as growth medium on the growth and the yield of white oyster mushroom (Pleurotusostreatus). The research was conducted at Boyaoge village, Palu, Central Sulawesi from September to November 2013. This study used experimental method by Completely Randomized Design (CRD) with five sawdust as treatments, i.e; Palapi (Heritierasp.) (M1), Cempaka (Elmerrilia sp.) (M2), Bayur (Pterospermumjavanicum) (M3), Gmelina (Gmelinaarborea) (M4) and Durian (Duriozibethinus) (M5).The results showed that sawdust significantly affected mycelium initiation, growth of mycelium on bag log, primordial initiation, the number of fruiting bodies, stem length, and cap diameter of mushroom. Mushrooms grew best on the sawdust mediumofCempaka (Elmerrillia sp.). The results of the study showed that sawdust of Cempaka (Elmerrillia sp.) gave the best growth with mycelium initiation was 4 days, growth of mycelium on bag log was 27,5 days, primordial initiation was 34,8 days, the number of fruiting bodies was 2, stem length was 4,9 cm, cap diameter of fruiting bodies was 9,7 cm, fresh weight of fruiting bodies was 11,4 g and dry weight of fruiting bodies was 7,5 g. Keywords: Growth Medium, Sawdust, Oyster Mushroom (Pleurotus ostreatus).